Input Controls in the Public Sector : What Does Economic Theory offer? (IMF Working Papers; Working Paper ;, 1988)
This paper reviews the economic literature on bureaucratic behavior, the theory of the firm, and agency theory and its application to the public sector, to determine whether any lessons can be drawn regarding how far governments should go in delegating control over inputs to public sector managers. Against a background survey of country practices, the paper concludes that input controls are one of a number of ways of dealing with the agency problem of trying to ensure that bureaucrats act in the interests of the government. Other methods can be, and have been, used for dealing with moral hazard-type agency problems, but features of current budgetary systems make it more difficult to deal with inputs that have implications for future resource use.